Pragmatical utilization of beneng taro (Xanthosoma undipes) based on local knowledge of the community of Mount Karang, Pandeglang, Indonesia - GUT WINDARSIH; AZIZAH FAUZIAH RAHMA; DENI MULYANA; MUHAMMAD RIFQI HARIRI; INA ERLINAWATI; INDIRA RIASTIWI; MUHAMMAD EFENDI (Society for Indonesian Biodiversity, 2023)
Abstract. Windarsih G, Rahma AF, Mulyana D, Hariri MR, Erlinawati I, Riastiwi I, Efendi M. 2023. Pragmatical utilization of beneng taro (Xanthosoma undipes K.Koch) based on local knowledge of the community of Mount Karang, Pandeglang, Indonesia. Biodiversitas 24: 6415-6424. Beneng taro (Xanthosoma undipes K.Koch) belongs to the order Arales and family Araceae. It is one of the staple crop commodities cultivated extensively in Mount Karang, Pandeglang District, Banten, Indonesia. This research aimed to assess the utilization of beneng taro by the local community in Mount Karang. The study was classified as descriptive research. The research used exploratory surveys and participatory rural appraisal as methodological approaches. Data collection techniques were collected through interviews, questionnaires, observations, and documentation. Moreover, 30 participants were selected using purposive sampling and snowball sampling methods. The plants were sampled randomly, 5 per location, to observe morphological traits. The findings of this study indicate that there are two local cultivars of beneng taro found in Mount Karang, including green leaf sheath and red leaf sheath cultivars. All beneng taro plant parts possess significant economic worth, including leaf blades, leaf sheaths, petioles, corms, cormels, and exudates. This plant is frequently used for food and beverage, cigarettes, medicinal ingredients, fabric production, crafts, organic fertilizer, livestock feed, fish pellets, and decorative plants. However, beneng taro with green leaf sheath is more widely cultivated in the area and consumed for food and beverage.